COGNITIVE INTERJECTION IN INDONESIAN AND JAPANESE - Shalika, Mayang Putri; Mulyadi, Mulyadi (HUMANIKA, 2019)
Cognitive interjection conveys a message that is more oriented to cognition or thought, namely something that is known as information and becomes new knowledge. This type of Interjection is different from emotive interjection and volitive interjection. This study aims to reveal the form and meaning of cognitive interjection in Indonesian and Japanese. This research is a kind of qualitative descriptive research and at the data collection stage the method used is the refer method. Natural Semantic Metalanguage Theory (NSM) is used to identify and describe the form and meaning of cognitive interjection in both languages. The forms of cognitive interjection in Indonesian are: Aha, aah, wah, ooh, hmm, oopps, hah, well, well. In Japanese the forms of interjection are: Aa (ã‚ ã‚), Yaa (ã‚„ ã‚), Maa (ã¾ ã‚), Aa (ã‚ ã‚), Eeto (ãˆ ãˆ ã¨), Ee (ãˆ ãˆ), Are (ã‚ ã‚Œ), Sora (ã ã‚‰). This study found groups of meanings for cognitive interjection, which were divided into interjection expressions of thought, interjection of expressions of difficulty, interjection of agreed expressions, interjection of expressions only knowing something, interjection of expressions of distrust, interjection of expressions of guilt, interjection of expressions recalled. Keywords: Cognitive Interjection, NSM (Natural Semantic Metalanguage), Cognition